Assessment tool for best practices of construction waste minimization / Noor Rizallinda Ishak and Siti Akhtar Mahayuddin - Ishak, Noor Rizallinda; Mahayuddin, Siti Akhtar (https://journal.uitm.edu.my/ojs/index.php/MySE/issue/view/434, 2025)
A rise in residential construction projects to meet housing demand has inevitably generated substantial amounts of waste. Ineffective waste management and illegal dumping have worsened this problem. This research aims to develop an assessment tool for best practices of construction waste minimisation. The objectives are: 1) To identify criteria and indicators for best practices in waste minimisation, 2) To determine the best practices indicator, and 3) To develop an assessment tool. The study was conducted in Klang Valley which has the highest number of residential. A mixed-method approach was used, combining qualitative and quantitative methods. For the first objective, semi-structured interviews were conducted with 11 construction practitioners such as Site Engineers and Site Managers. By using thematic analysis the results revealed 44 best practice indicators. For the second objective, a questionnaire survey was distributed to 153 construction practitioners in the Klang Valley area focusing on residential projects. The survey was analysed using descriptive analysis and the Relative Important Index (RII) to develop an assessment tool. The analysed results were ranked with the RII. The top rank was "Effective communication on-site" and the lowest was "Appointment of labour just for waste management". Then, the ranking and indicators were used to calculate the weightage for best practices of construction waste minimisation. The weighted scores were grouped into “Excellent,” “Good,” “Fair,” and “Poor”. The assessment tool provides a performance percentage chart. In conclusion, the assessment tool, provides ratings and performance charts, to guide contractors in improving waste management strategies and setting performance benchmarks.